Sistem Informasi Manajemen Dalam Pengambilan Keputusan Pada Dinas Komunikasi Dan Informatika Kabupaten Tulungagung - Titik Winarti; Arisyahidin Arisyahidin; Imam Baehaki (Universitas Islam Kadiri, 2020)
This research describes the utilization of management information system at Organization of Regional Devices. Taking the example of Transportation Department of Communications and Informatics of Tulungagung Regency, this research specifically explains the role of management information system (SIM) to the decision of Head of Service. The purpose of this study is to determine the role of management information systems in decision making used by Head of Department and Head of Government. Decision-making is the most important Leadership role and the availability of reliable sources of information is a key component in leadership decisions within an organization. In this research use qualitative research method with descriptive approach. Informants in this study are Head of Department, Secretary, Head of Division, Section Chief and Staff of Transportation Department of Communications and Informatics of Tulungagung Regency that is directly related to this research topic. Data and information gathering is done by interview. The results of this study indicate that the Management Information System in decision-making owned by the Department of Transportation Communications and Informatics Tulungagung District utilize Management Information Systems, to help and facilitate their work much less related to decision making, although sometimes the decision is not necessarily through a computer system. But sometimes a physical decision is made by the Head of Service.